Circulating HO-1 levels are not associated with plasma sFLT-1 and GT n HMOX1 polymorphism in preeclampsia - Sandrim, Valeria [UNESP]; Coeli-Lacchini, Fernanda Borchers; Tanus-Santos, Jose Eduardo; Lacchini, Riccardo; Cavalli, Ricardo Carvalho (Taylor & Francis, 2019)
Objectives: We aimed to assess the plasma HO-1 level and its interrelationship with the plasma sFLT-1 level in preeclamptic and healthy pregnant women with different variants of microsatellite polymorphism (GTn) located in the promoter region of the HMOX-1 gene. Methods: HO-1 and sFLT-1 were measured by ELISA. HMOX1 genotyping was performed using fragment analysis. Results: We found similar and higher levels of plasma HO-1 and sFLT-1, respectively, in preeclampsia. Similar genotypes and alleles frequencies were found in both groups and the absence of modulation of HO-1 levels by genotypes were observed. Conclusion: The plasma HO-1 levels are not increased in preeclampsia women and neither related to sFLT-1 levels and GT n polymorphism.
Keywords: HMOX1 genotyping; oxidative stress; plasma HO-1; plasma sFLT-1; polymorphism; Preeclampsia